Sedimentation in the Rupnarayan River Volume 1: Hydrodynamic Processes Under a Tidal System - Kumar Maity, Swapan (SpringerBriefs in Earth Sciences,, 2018)
This book explains the causes, mechanisms and dimension of sedimentation in the Rupnarayan River, which offers a representative example of a tidal river combining fluvial and marine processes. The book is unique in addressing all the hydrodynamic characteristics of the river, especially the tidal impact, sediment load and textural characteristics of the sediments. ; The data presented here was gathered through continuous field monitoring using state-of-the-art techniques and robust laboratory analysis, and will help readers develop a systematic understanding of sedimentation processes. As such, the book offers a valuable resource for all students and researchers conducting research on fluvial geomorphology and sedimentology. In addition, the outcomes it presents will benefit engineers, hydrologists, planners and other authorities affected by a number of aspects related to sedimentation.